Radiative tail of the three-particle light-cone distribution amplitudes for the Λ b baryon in HQET - Thorsten Feldmann; Daniel Vladimirov (Journal of High Energy Physics)
Abstract We calculate the so-called radiative tail for the three-particle light-cone distribution amplitudes (LCDAs) of the Λ b baryon, following from the short-distance expansion of the defining light-ray operators in heavy-quark effective theory (HQET). To illustrate the effect of the radiative tail, we introduce a simple (model-dependent) extrapolation to large distances (respectively small momenta), which preserves the analytic properties of the LCDAs in HQET. We observe a similar qualitative behaviour as has been discussed for the B-meson case.